Effectiveness of Potassium Oxalate mouthrinse in treating dentinal hypersensitivity - Maddula Y S L N V, Amruthavalli; Nalamati, Shiva Keerthi; Gummadi, Anusha; Gorle, Santhi; Nimmala, Sriram Naidu; Katru, Sreekar (International Journal of Dental Materials, 2024)
Background: Dentinal hypersensitivity is a prevalent oral condition characterised by a short, sharp pain in response to chemical, thermal, tactile, or osmotic stimuli. It can be treated with the in-office application of potassium oxalate (KO). This study assesses KO mouthrinse for home use. Aim: To assess the efficacy of Vantej® mouthrinse, containing potassium oxalate (KO), in reducing dentinal hypersensitivity when used in combination with regular brushing for three months. Materials and methods: In this double-blind, parallel group-controlled study, participants with dentinal hypersensitivity were randomly assigned to Group 1, which used the KO mouthrinse, and Group 2, which used a placebo. The participants used their assigned mouthrinses for three months. The success of each participant was measured using the mean cold air stimulus response (VAS) and Schiff sensitivity score. Results: A significant decrease (p=0.00) in hypersensitivity in patients treated with potassium oxalate mouthrinse was observed. Conclusion: Mouthrinse containing 1.4% potassium oxalate consistently demonstrated effectiveness in reducing dentinal hypersensitivity after three months of use.